2015
DOI: 10.1063/1.4928968
|View full text |Cite
|
Sign up to set email alerts
|

Energy conversion and momentum coupling of the sub-kJ laser ablation of aluminum in air atmosphere

Abstract: Energy conversion and momentum coupling using nano-second 1-μm-wavelength pulse laser irradiation on an aluminum target were measured in air and nitrogen gas atmospheres over a wide range of laser pulse energies from sub-J to sub-kJ. From the expansion rate of the shock wave, the blast-wave energy conversion efficiency, ηbw, was deduced as 0.59 ± 0.02 in the air atmosphere at an ambient pressure from 30 to 101 kPa for a constant laser fluence at 115 J/cm2. Moreover, the momentum coupling of a circular disk tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 26 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Therefore, it is necessary to investigate the plasma plume properties in combination with the impulse coupling properties. In fundamental studies of pulsed laser ablation (PLA), the plasma plumes generated by laser ablation can usually be studied using interferometry [14], a Faraday cup [15], a Langmuir probe [16], shadowgraphy [17], self-emission imaging using fast photography [18], or optical emission spectroscopy [19]. Each of the plasma plume diagnostic methods has its own characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the plasma plume properties in combination with the impulse coupling properties. In fundamental studies of pulsed laser ablation (PLA), the plasma plumes generated by laser ablation can usually be studied using interferometry [14], a Faraday cup [15], a Langmuir probe [16], shadowgraphy [17], self-emission imaging using fast photography [18], or optical emission spectroscopy [19]. Each of the plasma plume diagnostic methods has its own characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have discussed how to generate the doughnut beam [10][11][12]. In a previous study by Xie et al, a numerical study was done in the case studies where there was not lateral offset [13], and it was suggested that the impulse could be higher with a doughnut beam than with a singlespot beam [14,15], owing to the shock focusing effect [16][17][18][19]. However, such a shock focusing effect on the impulse enhancement has not been verified experimentally.…”
Section: Introductionmentioning
confidence: 99%